A Monolithically Integrated Gallium Nitride Nanowire/Silicon Solar Cell Photocathode for Selective Carbon Dioxide Reduction to Methane. Issue 26 (24th May 2016) - Wang, Yichen; Fan, Shizhao; AlOtaibi, Bandar; Wang, Yongjie; Li, Lu; Mi, Zetian
Abstract: A gallium nitride nanowire/silicon solar cell photocathode for the photoreduction of carbon dioxide (CO2 ) is demonstrated. Such a monolithically integrated nanowire/solar cell photocathode offers several unique advantages, including the absorption of a large part of the solar spectrum and highly efficient carrier extraction. With the incorporation of copper as the co‐catalyst, the devices exhibit a Faradaic efficiency of about 19 % for the 8e − photoreduction to CH4 at −1.4 V vs Ag/AgCl, a value that is more than thirty times higher than that for the 2e − reduced CO (ca. 0.6 %). Abstract : Yes we GaN : A silicon solar cell photocathode with a GaN nanowire for the photo‐reduction of CO2 is reported. Such a photocathode offers the absorption of a large part of the solar spectrum and highly efficient carrier extraction. With the incorporation of Cu as the co‐catalyst, the devices exhibit a Faradaic efficiency of about 19 % for the 8e − photoreduction to CH4 .